Re-Design Packaging Cookies Deanke Padang - Audina Gusma Triana; Fauzan Aulia (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
Deanke is an artisanal cookies business that sells online. The products offered by Deanke are specific in the field of cookies and brownies. The purpose of this Final Project is to produce a new packaging design for Deanke's cookies, by maximising the function of packaging as a means of product communication and branding to consumers so as to increase Deanke's brand awareness. The method used in this design is the 4D method consisting of Define, Design, Develop, and Disseminate with data analysis method through SWOT Analysis. This design will produce the main media in the form of packaging and supporting media in the form of social media, menus, thank cards / gift cards, stickers, posters and x-banners which are tested for feasibility to the target audience. It is expected that through this packaging design can achieve the main objectives in maximising the function of packaging, through a better packaging structure and increasing Deanke's brand awareness.